Excited Catatonia in Autism Spectrum Disorder: A Case Series - Burns, Nora Kathleen; Grissett, Kathleen; Macaluso, Marc; Raza, Mohsin; Gracious, Barbara (Frontiers in Psychiatry, 2021)
Intro: Autistic catatonia is an under-recognized debilitating syndrome with long-lasting negative effects for families, healthcare workers, and high-cost to the healthcare system. In this report, we describe two cases of excited catatonia in young men diagnosed with autism. Both endured a delay to diagnosis and difficulty to obtain appropriate treatment. Main concern: Each patient had a change in behavior from their baseline but with differences in severity and onset. The diagnosis in the first patient was made after only three months as the change was dramatic and sudden. Yet, despite a confirmed diagnosis, it was difficult to treat as the importance of M-ECT was not recognized by the clinicians. The second patient had been suffering for more than five years with a slow progression of worsening aggressive symptoms. The aggression was so uncontrollable that the patient required sedation, intubation and ECT treatment en bloc. Both suffered from agitation, unprovoked aggression, urinary incontinence, stereotypic and OCD behaviors and compulsive masterbation. Primary Diagnosis, intervention/outcomes: Both patients were diagnosed with autism, one high-functioning, attending high school and working a part-time job, the second low-functioning, nearly non-verbal, isolated to home and ABA school. The first patient’s diagnosis of catatonia was only suspected after five psychiatric admissions and more than 20 medication trials. Lorazepam challenge was effective, he was treated with a short series of ECT but each time the treatments were tapered, the aggression returned. Ultimately, stabilized on weekly ECT. The second patient’s behavior was escalating over a five month period, to the point, the aggression was uncontrollable. He presented to the ED under involuntary hold and the behavior could not be stabilized to the point that emergent ECT was initiated. Conclusion: Two cases of autistic catatonia diagnosed and treated within a year time span at a small community hospital indicates that this diagnosis is more common than previously recognized. We propose screening all patients with neurodevelopmental disorders with the Bush-Francis and Kanner scales to diagnose and treat them appropriately.